Get Your Yams, Barbados, B.W.I. - Knight’s Ltd. (The Main Library, University of the West Indies, Cave Hill Campus, Barbados is responsible for making this digital resource available., 2023)
This image shows a female vendor carrying a tray of yams on her head. The lady is dressed in the fashion typical of the times and her occupation. She is barefooted. In the background, is a house with wooden doors and a verandah. There are potted plants on the outside of the house. This is a divided back postcard. Back of the Postcard Knights Ltd Y 10 £7 (Handwritten in Pencil)
Vertical, Black and white, “3 ½” x 5½ ”
Keywords: Occupations; Clothing and dress; Street Vendors; Yams; Food vendors; Women; Houses; Architectural elements; Hawkers; Hucksters